2010
DOI: 10.1089/pho.2009.2566
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Topical Aminolevulinic Acid Photodynamic Therapy for the Treatment of Verruca Planae

Abstract: PDT, utilizing the topical application of 10% ALA, has a good result and excellent cosmetic effects for the treatment of verruca planae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 4 publications
1
30
2
1
Order By: Relevance
“…Eighteen adults treated with azone followed by ALA-PDT had a clearance rate of 94.4% after two sessions. Twelve patients had transient pigment changes, but no scarring resulted (28).…”
Section: Photodynamic Therapymentioning
confidence: 92%
“…Eighteen adults treated with azone followed by ALA-PDT had a clearance rate of 94.4% after two sessions. Twelve patients had transient pigment changes, but no scarring resulted (28).…”
Section: Photodynamic Therapymentioning
confidence: 92%
“…Only a small number of controlled trials are available on this agent, and results are variable. [26][27][28] Immunomodulation Failure to eliminate epidermal cells infected with the human papillomavirus represents a failure of cell mediated immunity and therefore presents the rationale for stimulating cell mediated immunity. Various strategies have been attempted.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…A total of seven studies on PDT for wart treatment were found (Table ) with 109 patients treated. Six studies utilized ALA as a photosensitizer while one study used MAL.…”
Section: Resultsmentioning
confidence: 99%